A Discussion of Learning Maritime English by Utilizing Authentic Video in Speaking Skill - Hayatun Nufus; Usman Kasim (Universitas Syiah Kuala, 2018)
This study describes the utilization of authentic video by maritime English teachers in speaking class, the challenge often faced by the teacher in utilizing authentic video and students’ responses toward utilizing authentic video. The participants of this study were 100 cadets and four maritime English teachers. Quantitative and qualitative methods were employed and obtained from observation sheet, interview and questionnaire. The data result found that: (1) four observed teachers implemented the same way in utilizing video; (2) the teachers did the three phases in video application, such as Pre-Viewing, Viewing and Post-Viewing Activity; (3) there are still lack of activities toward the video material; and (4) there are several problems faced by the teacher in utilizing authentic video are as follows: selecting the video that fits the topic, the limitation of video archive, audio-visual tools and avoiding the ‘nothing new” video syndrome among the students. (5) the students’ responses toward authentic video application was very positive. There are 55 students who chose strongly agree option by means authentic video can give them example of working scope later. 56 students stated that learning English by using video can make their knowledge stay longer. 51 students like learning English by using video. Besides, 69 students stated that their teacher often uses authentic video while teaching English. It is suggested that the teachers should be more creative in utilizing authentic video and participate in workshops related to learning material.